First Generation Korean American Parents’ Perceptions of Discipline - Kim, Eunjung (2007)
Nurses not only need to be familiar with the professional guidelines of discipline and but also be aware of variances in styles of acceptable discipline across cultural groups. The goal of this study was to explore cultural influences in relation to (1) first generation Korean American parents’ perceptions of common discipline strategies in the United States and (2) discipline strategies commonly used among first generation Korean American parents. Inductive content analysis was used to analyze interview data from seven first generation Korean American parents. Derived themes indicated that parents considered spanking/hitting and less hugging/kissing as Korean style and time out, using a sticker chart, hugging/kissing, removing/adding privileges, and giving chores as American style. Recent immigrant parents were not familiar with common positive discipline strategies in the United States. As they adapted to the mainstream society, they discontinued what they perceived to be negative aspects of Korean style and adopted positive aspects of American style. They were sensitive to children’s views on discipline and they experienced communication difficulties with children. These findings indicated that Korean American parents’ perceptions on discipline strategies were shaped by living in two cultures and were different from the western viewpoints.